Characteristics of Orthodontic Appliance Users based on Demographics, Self-Perception, Psychosocial, and Oral Disorders (Study Among Undergraduate Students in West Jakarta) - Yovanka, Vanessa; Kusnoto, Joko; Andayani, Lia Hapsari (Journal of Indonesian Dental Association, 2023)
Introduction: Awareness of malocclusion and the importance of orthodontic treatment continue to increase, in order to improve dentofacial appearance, psychosocial factors, and quality of life. Orthodontic treatment can be done using conventional fixed appliances, or removable appliances called clear aligners, that has an upsurge in demand recently. Previous studies have evaluated the advantages and disadvantages of orthodontic treatment types, yet there are still lack of findings regarding the characteristic of user. Objective: This study aims to describe the characteristics of orthodontic appliances users based on demographics, self-perception, psychosocial, and oral disorders, among undergraduate student in West Jakarta. Methods: This cross-sectional study was conducted in October until December 2022. The study population covered 7 universities located in West Jakarta. Sample consist of 201 undergraduate students taken by purposive sampling. Self-administered questionnaire, that had been validated was used to obtain sociodemographic data and factors that can affect the preference of orthodontic appliances. Results: The most common orthodontic appliances used is fixed orthodontic appliances (79.6%) that was installed by orthodontists (58.8%). Most students using orthodontic appliances were female (76.2%), aged 17-25 years (99.4%), and currently undergoing study in non-medical faculty (71.9%). Students were highly aware of their dental arrangement (90.5%). They thought that their facial and dental aesthetics (97.5%) and social interaction (66.2%) will improve after orthodontics treatment, though they were not sure about getting better career opportunities (51.7%). Conclusion: Fixed orthodontic appliances still become the main preference among undergraduate university students in West Jakarta. Awareness and dissatisfaction of their dental arrangements were substantial as well as the desire that facial and dental appearance will improved after treatment. Orthodontic treatment was considered as way to enhance social interaction social attractiveness.